Análise do conhecimento pedagógico do conteúdo de professores de educação física: pré-escola e anos iniciais do ensino fundamental - Zanotto, Luana (2019)
This research comprises Physical Education teaching practice and its field of investigation is the early years of Basic Education, comprehended by a) Children’s Education (Preschool), and b) Elementary School (early years), in this study named Children’s Physical Education (CPE). This study aims to analyse teacher’s pedagogical content knowledge; then, relate to how the knowledge base organizes the pedagogical practice. This knowledge base in teaching refers to the subject, the content, the context, and general pedagogical knowledge. To achieve that, the project was based on a qualitative approach. In the first stage, 14 teachers from different schools in a city on the countryside of São Paulo state, Brazil. For the data collection, an extension activity was proposed to a specific group of participants during their Collective Pedagogical Work Time. The second stage consisted in interviews with four teachers in the interest of the correlation of a pedagogical content knowledge in teaching; as well as collected information regarding the vertical articulation of CPE’s curriculum. The results showed that teachers are aware of the subject - the child - from the direct contact with them. The subject’s knowledge reveals when the teacher adapts the classes according to their demands and the expectations created by the teachers themselves. Also, regular and cultural games consist the content applied on CPE, which highlights a sufficient knowledge expressed by the teachers, mostly in their didactic application of this theme. The children’s context concerned the teachers as well, and reflected on their pedagogical practice. On the other hand, the awareness about other schools, the teaching community, and social factors were less present in their reports, indicating small contributions for their pedagogical content knowledge. Also, interdisciplinary activities and continuity in teaching were identified, although no effective measures were taken for a vertical articulation of the curriculum. The conclusion points to an array of practices for teacher’s professional development through a continuing education process specific and contextualized for each teaching profile.